Research on Single-Event Effect Hardening Method of Transverse Split-Gate Trench Metal-Oxide-Semiconductor Field-Effect Transistors - Mengtian Bao; Ying Wang; Jianqun Yang; Xingji Li (Micromachines)
In this work, the single-event burnout (SEB) effect and degradation behaviors induced by heavy-ion irradiation are investigated in a 120 V-rated transverse split-gate trench (TSGT) power metal-oxide-semiconductor field-effect transistor (MOSFET). Bismuth heavy-ions are used to conduct heavy-ion irradiation tests. The experimental results show that the SEB failure threshold voltage (VSEB) of the tested sample is 72 V, which only accounts for 52.6% of the actual breakdown voltage of the device. The VSEB value decreased with the increase in the flux. The simulation results show that the local “hot spot” formed after the incident heavy ion is an important reason for the drain current degradation of TSGT MOSFETs. To improve the single-event effect tolerance of TSGT MOSFETs, an SEB hardening method based on process optimization is proposed in this paper, which does not require additional customized epitaxial wafers. The simulation results show that, after SEB hardening, the VSEB is increased to 115 V, which accounts for 89.1% of the breakdown voltage.